EVALUASI KINERJA CARGO OIL STRIPPING PUMP TYPE BORNEMANN TWIN SCREW 2HM4200-100 DI KAPAL MT. NONI T - Kayadoe, Yuliens Anggin; Lekatompessy, Roy R; Huka, Graciadiana I; Hahury, Sanny (Journal Mechanical Engineering, 2024)
Evaluation of the performance of cargo oil stripping pumps on the Mt. Noni T ship is needed for smooth loading and unloading of avtur at PT Pertamina Prata Niaga Integrated Wayame Ambon. Pumps that operate continuously will experience a decrease in work. This can be caused by several factors, namely the age of the pump, and the level of roughness of the pipe that causes an increase in head loss. The purpose of this study is to evaluate the performance of cargo oil stripping pumps on the MT. Noni T. The method carried out in the study uses a quantitative method with 2 variables. The independent variable is the input power and output power of the pump while the bound variable is the efficiency of the pump. The data obtained consisted of primary data and secondary data. The methods used when collecting data are interview, observation, and documentation methods. The result of this study is that there is a decrease in pump efficiency which was initially 100% to 80% influenced by the life of the pump and its operating time. Suggestions that can be given are Conducting periodic inspections of the pump to prevent damage that may occur in the future and Conducting inspections of the pump drive motor so that the pump works properly.Keywords: Screw, pump, efficiency, tanker, Flow.